Communicable Diseases Intelligence volume 17 issue 20 - 4 October 1993 - whole issue - No authors listed, (Communicable Diseases Intelligence, 1993)
Whole-issue pdf, comprising: Original Articles: World Malaria situation in 1991 Overseas Briefs Communicable Diseases Surveillance Virology and Serology Reporting Scheme Australian Sentinel Practice Research Network [ASPREN] Sterile Sites Surveillance (LabDOSS) National Notifiable Diseases Surveillance System, 5 September to 18 September